Role of Breaking News in Creating Anxiety among TV Viewers in Lahore: An Analysis of Cultivation Theory - Waheed, Aqdus; Iqbal, Naveed; Arain, Shahbaz Ali (Journal of Development and Social Sciences, 2025)
This study is an effort to understand the effects of constant exposure to television breaking news on the state of anxiety among the viewers in Lahore. The research undergoes the Cultivation Theory, which explores how a rise in protracted exposure to unexpected and tense news contributes to psychological fragility. Crises such as political unrest, violence, and disasters are a part of the breaking news, which may increase panic and ambiguity among people. A survey was also done on 400 regular TV news watchers ages 20-45 and quantitatively. Spss was used to analyse data, with the aid of Chi-square tests to evaluate the correlation between the consumption of breaking news and the level of anxiety. Results indicate that there is a positive significant correlation between repeated exposure to breaking news and anxiety. The theoretical argument that long-term media use influences both the emotional conditions and the threat perception was supported by the heavy viewers which reported more anxiety compared to moderate and light viewers. Encourage responsible journalism, diminish sensationalism, enhance media literacy training and offer mental health support and awareness programmes to enable the viewer process news information critically as well as dealing with anxiety